In Situ Coupling of Single Molecules Driven by Gold‐Catalyzed Electrooxidation. (11th July 2019) - Zang, Yaping; Stone, Ilana; Inkpen, Michael S.; Ng, Fay; Lambert, Tristan H.; Nuckolls, Colin; Steigerwald, Michael L.; Roy, Xavier; Venkataraman, Latha
Abstract: A single‐molecule method has been developed based on the scanning tunneling microscope (STM) to selectively couple a series of aniline derivatives and create azobenzenes. The Au‐catalyzed oxidative coupling is driven by the local electrochemical potential at the nanostructured Au STM tip. The products are detected in situ by measuring the conductance and molecular junction elongation and compared with analogous measurements of the expected azobenzene derivatives prepared ex situ. This single‐molecule approach is robust, and it can quickly and reproducibly create reactions for a variety of anilines. We further demonstrate the selective synthesis of geometric isomers and the assembly of complex molecular architectures by sequential coupling of complementary anilines, demonstrating unprecedented control over bond formation at the nanoscale. Abstract : Azobenzolderivate können selektiv aus Anilinen durch eine goldkatalysierte oxidative Kupplung erhalten werden, die durch das lokale elektrochemische Potential an einer Gold‐STM‐Spitze angetrieben wird. Die Produkte wurden durch Einzelmolekül‐Leitfähigkeitsmessungen bestimmt und mit ex situ hergestellten Azobenzolderivaten verglichen.